MANAGEMENT OF AN ESTABLISHMENT OF HIGHER EDUCATION BY MEANS OF INFORMATION-AND-COMMUNICATION TECHNOLOGIES - DANYLYUK, Serhiy (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
General directions of improving the management of educational organizations are studied in the paper. Obtaining and applying information resources for education is also analyzed. Development of information technology for objectives of education and for management purposes is shown. Transfer of knowledge in educational and managerial processes is highlighted. The use of information units as components of technology and information resources is grounded